(3GdCfhGQ GddGFMI aj CSQGQ ShQI GdaGJMIs - (3CHh GdHQcGJ eMeO Hf Gdejdb GdTGaYj GdTGPdjs ((3eOQSI GdcgGQHI (B_ (3GdbGgQg GdeYRjg s)
(3ChdgG (B:s
(3CeG HYO abO hQO Ydi cJGHc JTjQ ajg Edi eG SeYJg efi ai HYV GdeLGdS ef GdJfHjg Ydi eG JVefJg ShQI GdaGJMI ef LhGeY GdeYGfi GdfaGFS hSejJg GdGfhGQ GddGFMI ef CSQGQ GdaGJMI s
(3BNQgG (B:s
(3Efi CSdC Gddg JYGdi Cf jhabfi hSGFQ GdeSdejf deG jVQGg ef GdYde hGdYed hMSHfG Gddg hfYe Gdhcjd gPG BNQ GdBfhGQ GddGFMI s
(3cJHJ HYV cdeGJgG HGdMeQIs
(3YdjgG JUMjMGJ hJbjjOGJ hai BNQgG ELGRI GdeDda HQgGf GdOjf EHQGgje Hf YKeGf SfI (B797(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCMbGa eLehYI Bd jMi (B((3JaSjQ (B- (3JQje (B66) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs